PENERAPAN BINA DIRI DENGAN TEKNIK MODELLING UNTUK MENINGKATKAN PERILAKU ADAPTIF SISWA KELAS VIII C SEKOLAH LUAR BIASA YPPABK NGAWI - Eny Setyowati Setyowati; Anisah Binti Solekah Solekah; Resa Andi Pratiwi (Kurikula : Jurnal Pendidikan, 2021)
ABSTRACT This research is written to increase effectiveness tunagrahita learning activities in VIII C YPP ABK Ngawi can behave adaptive behavior and leave non adaptive. The kind of research used is case study, that is a discriptive and analysis a specified phenomenon social as individual or unit, group an intitution or community. The implementation of a development modelling to facilitate students in understanding and practice material provided by teacher making it the adaptive students behavior seen from the behavior changes and attitudes interact social students in all teachers or by part of his class, they didn’t even conduct behavior non adaptive as before. Keywords : Self development, modelling technique, adaptive behavior